Magnetic Nanostructures in Modern Technology Spintronics, Magnetic MEMS and Recording - Azzerboni, Bruno; Asti, Giovanni; Pareti, Luigi; Ghidini, Massimo; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
A team of outstanding scientists in the field of modern magnetic nanotechnologies illustrates the state of the art in several areas of advanced magneto-electronic devices, magnetic micro-electromechanical systems and high density information storage technologies. The physics and chemistry of nano-scale systems have made rapid advances and there are real prospects of translating exciting scientific findings into a new generation of processes and high technology products with a potential impact on several industrial sectors. In particular the development of nano-structured magnetic materials plays a leading role in the increasing miniaturization of devices with superior performances. The application areas considered are: i) "magneto-electronics", where the control of electron spins in magnetic hetero-structures offers new and improved functionalities in devices of integrated digital electronics. Magnetic random access memories, MRAM are among the principal applications for new non-volatile RAM with fast dynamics, toward the pico-, femto-second range. ii) "magnetic MEMS" (micro-electro-mechanical systems), which are the integration of mechanical and electro/ferromagnetic elements (micro-actuators and sensors) with conventional electronics MEMS, promise a revolution in several product categories. In fact the proposed integration enables the development of smart products, where sensors can gather information from the environment by measuring thermal, magnetic, electric, mechanical, biological chemical, optical characteristics and the electronic section processes the information and the actuator promotes the action realizing a complete control of the environment. iii) "Magnetic recording" is a leading technology in the information storage domain and the most relevant application in the field of magnetics, showing surprising continuous progress over several decades towards the limit of terabit per square inch of areal density.>.
Spin-Polarized Current and Spin-Transfer Torque in Magnetic Multilayers -- Spin-Transfer-Driven Magnetization Dynamics -- Micromagnetic Modeling of Magnetization Dynamics Driven by Spin-Polarized Current: Basics of Numerical Modeling, Analysis of Confined Systems -- Micromagnetic Modeling of Magnetization Dynamics Driven by Spin-Polarized Current: Analysis of Nonconfined Systems -- Micromagnetic Modelling of Magnetization Dynamics Driven by Spin-Polarized Current: Stability Diagrams and Role of the Non-Standard Effective Field Contributions -- Magnetic Rings: A Playground to Study Geometrically Confined Domain Walls -- Magnetic Microsystems: MAG-MEMS -- MEMS Inductors: Technology and Applications -- Magnetic Particle Handling in Lab-on-a-Chip Microsystems -- High Performance ?-Magnets for Microelectromechanical Systems (MEMS) -- Magnetic Imaging Films -- Energy Exchanges of Magnets with the Environment -- Magnetic Data Storage: Past Present and Future -- Quantum effects in interacting electron systems: The role of spin in the interaction and Entanglement in Mesoscopic Systems -- Magnetism in one-dimensional metal systems.
Keywords: Engineering; Computer memory systems; Computers; Magnetism; Magnetic materials; Nanotechnology; Materials -- Surfaces; Thin films; Engineering; Nanotechnology and Microengineering; Theory of Computation; Nanotechnology; Magnetism, Magnetic Materials; Surfaces and Interfaces, Thin Films; Memory Structures; Electronic books